Effect of Oxidative Torrefaction on Characteristics of Treated Corncob Pellets - Tanakorn Tanyaket (2020)
© 2020, Chinese Mechanical Engineering Society. All right reserved. Oxidative torrefaction of corncob pellets was carried out in a fixed bed thermal reactor with 40±0.5 g of samples. All experiment works were performed under oxidative conditions with 0 to 18% oxygen in nitrogen atmosphere, temperatures at 220, 260, and 300℃ for reaction time of 5 to 20 min. Experimental results showed that mass yields were significantly reduced with increasing temperature at given oxygen concentration and reaction period. Similarly, increase in torrefaction time was found to significantly reduce mass yields. However, effect of oxygen content was not observed to affect mass loss markedly. In this work, change in chemical composition, energy density, water uptake and grindability were also investigated. Oxidative torrefaction was found to improve quality of torrefied biomass in terms of increased carbon content, higher heating value and water resistance, and reduced energy requirement for size reduction.